Effects of Melatonin Derivatives on Human Malaria Parasite Plasmodium falciparum - Srinivasan, Venkataramanujan; Zakaria, Rahimah; Mohamed, Mahaneem; M. Saleh, Rozieyati (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2014)
Melatonin’s function in modulating the circadian cycle of Plasmodium falciparum has been an intense investigation for the past 45 years. The stimulatory effects of melatonin on malaria growth, development and differentiation have been confirmed by numerous studies conducted in the past 40 years but the molecular mechanisms underlying melatonin stimulatory effects have been well understood recently. Melatonin has been identified as a “signal” essential for synchronization of malaria parasitic cell cycle. Melatonin has been shown to modulate the release of intracellular Ca2+ and cAMP in Plasmodium falciparum. In this context, melatonin receptor blocking agent luzindole has been shown to block melatonin’s actions in these intracellular events occurring in human malaria parasites. Recent studies have resulted in the synthesis and development of melatonin derivatives, compounds 7-11 and 12-16. Of these compounds 12, 13 and 14 were able to inhibit the Plasmodium falciparum growth and this serves as a promising lead for the development of future antimalarial compounds that will have rapid antimalarial actions with low toxicity. Some antimalarial drugs that have been patented are also summarized in this review.
Keywords: Plasmodium falciparum